Speech Prosody 2020 2020
DOI: 10.21437/speechprosody.2020-127
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in four Alemannic dialects and its influence on the respective varieties of Swiss Standard German

Abstract: Languages, dialects, and speakers have been found to show variability in articulation rate and speech rhythm. The present study examines whether temporal variability found between four Alemannic (ALM) dialects is also present in the same speakers' Swiss Standard German (SSG) varieties. The results suggest that ALM interferences are not systematic. Whereas in ALM dialects, Churspeakers show the quickest articulation rate and Brig speakers the slowest, amongst the SSG varieties, Zurich speakers articulated the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…When we look at temporal variables, things become a bit complicated. While previous research has found that ALM dialects differ statistically significantly regarding rhythmic measurements (Leemann et al, 2012;2014a;2014b;2018), this was not confirmed for SSG (Zihlmann, 2020b). What is more, on the speaker level, already Dellwo et al's (2015) study showed that interspeaker variation amongst ALM speakers is rather great, which has also been found in this study for both ALM and SSG regardless of their dialect background.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…When we look at temporal variables, things become a bit complicated. While previous research has found that ALM dialects differ statistically significantly regarding rhythmic measurements (Leemann et al, 2012;2014a;2014b;2018), this was not confirmed for SSG (Zihlmann, 2020b). What is more, on the speaker level, already Dellwo et al's (2015) study showed that interspeaker variation amongst ALM speakers is rather great, which has also been found in this study for both ALM and SSG regardless of their dialect background.…”
Section: Discussioncontrasting
confidence: 68%
“…On top of this, regarding the evidence that some temporal measurements stay stable when speaking a foreign language (de Jong, 2018;de Jong & Mora, 2019), this could not be confirmed for ALM and SSG articulation rates (AR) and the share of vocalic speech in percent (%V) as only 2 and 4 speakers, respectively, showed similar values in the 2 varieties. On average, neither AR nor %V showed statistically significant region-specific values in SSG (Zihlmann, 2020b). Furthermore, the speaker-specific evaluation reveals that some speakers even show more similarities with speakers of other dialects than with speakers of their own one, as it is the case for, e.g., the AR of BE01 and BE02 that are much more similar with the ones of VS01, GR09 or ZH08 than with the ones of BE03 or BE06.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations